Cultural and Natural Sites of Europe According to UNESCO List of World Heritage in Danger - Viktoriia Pilkevych (Європейські історичні студії, 2019)
The author studies UNESCO’s activities in the cultural sphere, especially the protection and preservation of cultural heritage around the world. There is World Heritage List. Sites must be of outstanding universal value and meet the special criteria to be included on this List. Countries are trying to include their cultural objects for protection. Cultural heritage is architectural works, works of monumental sculpture and painting, elements or structures of an archaeological nature groups of buildings which are of outstanding universal value. The World Heritage Committee is responsible for the implementation of the World Heritage Convention («Convention Concerning the Protection of the World Cultural and Natural Heritage»,1972), gives financial assistance and decides on the listing or deletion of properties in the List of World Heritage in Danger. The List of World Heritage in Danger informs the international community of threat and to encourage corrective action.